Transformasi Pendidikan Berbasis Pancasila di Era Digital : Tantangan dan Prospek Moralitas Generasi Z - Muhamad Ali Mahfudi; Agus Satrio Utomo; Zaka Khoirul Huda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The transformation of education in the digital era demands a strong moral foundation to ensure that technological advancement does not erode human values. Pancasila, as the ideological and ethical foundation of Indonesia, plays a crucial role in guiding educational transformation to remain rooted in national moral values. This study aims to analyze the relevance and implementation of Pancasila values in shaping the morality of Generation Z amid the digitalization of education. The research employs a qualitative method with a descriptive-analytical approach through literature review, policy analysis, and observation of students’ digital behavior. The findings indicate that the internalization of Pancasila values within the digital education ecosystem contributes to strengthening character, ethical responsibility, and national awareness among Generation Z. However, key challenges include the lack of moral value integration in digital content and weak role modeling within educational environments. In conclusion, Pancasila-based educational transformation is not merely a technological innovation but a moral process that requires synergy among the government, educators, and society to create a humanistic, ethical, and civilized digital ecosystem.